Foucault, the colonial experience and racism. Notes to decolonize the archive (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
As Achile Mbembe has established, the decentering or provincialization of Europe opens up new possibilities for critical thinking. Questioning the potential of Foucault’s thought to understand our current situation (particularly from Latin America) implies starting from this fundamental fact. In this context, characterized by the becoming black of the world, and based on the criticisms formulated by various authors of the de- and post-colonial perspectives, the question about the Eurocentric character of Foucault’s thought has become relevant. Just as Nancy Fraser has pointed out the "hidden abode" of Marx and has drawn from it a radical critique of capitalism, we consider it is necessary to point out the "hidden abode" of the genealogy of power in Foucault. In this sense, the article questions the elision of the colonial experience in the archaeo-genealogy of modern Man, in the genealogies of disciplinary and biopolitical technologies of power, and in the analytics of neoliberal governmentality. Finally, the work seeks to recognize the potential of Foucault’s thought and to point out, at the same time, the need to decolonize its archive.